Interdisciplinaridade e solidariedade em experiências cooperativas do MST - Alceu Ravanello Ferraro (Ciências Sociais Unisinos)
A research project on cooperative experiences made in settlements of the Movement of Landless Rural Workers (MST) in the municipality of Piratini, state of Rio Grande do Sul, and developed with the support of FAPERGS and CNPq and with the participation of researchers and students from three universities (UCPel, UFPel and UFRGS) made it possible to arrive at some conclusions about the relationship between interdisciplinarity and solidarity that characterizes the cooperative work pursued by the MST. 1) The settlers freely move through the fields of work, education and leisure (which the research focused on), ignoring borders between disciplines. 2) Interdisciplinarity emerges as the element capable of making the difference between the autonomous, solidary, self-managed cooperative work and the cooperative work that is heteronomous, subordinated, commanded by capital. 3) Thus, interdisciplinarity and solidarity in work, education and leisure (and one may assume that this also applies to other dimensions of life in small family-based farms) emerge as elements of one and the same substance that ground and presuppose each other.